El desarrollo de la pericia en los entrenadores españoles expertos en baloncesto. - Jimenez Saiz, S.; Lorenzo Calvo, A.; Ibanez Godoy, S. J. (Revista Internacional de Ciencias del Deporte, 2009)
The present study was designed to address two issues: first, to identify the different development stages that eight expert Spanish basketball coaches go through; and second, to determine the possible factors that have contributed to the formative or training, process of the expert coach. Qualitative data were gathered in semi-structured interviews. The coaches worked with the men`s first Spanish Basketball League ("ACB" league) or the Spanish national selection. Our findings reveal four stages in the coach development process. These stages were the consequence mainly of a gradual progression in thinking and reflective practice that enabled the coach to optimize the necessary skills for high performance. In addition, all the coaches interviewed reflected an intense dedication and commitment over many years to their work, as well as an ongoing quest for improvement.